2016
DOI: 10.15376/biores.11.4.10483-10496
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-assisted Mechanical Fibrillation of Bleached Spruce Kraft Pulp for Producing Well-dispersed and Uniform-sized Cellulose Nanofibrils

Abstract: Cellulose nanofibrils (CNFs) are bionanomaterials with many promising properties and great potential in composite applications. Herein, welldispersed and uniform-sized cellulose nanofibrils were successfully obtained from commercially bleached softwood kraft pulp, resulting in yields of 79.15% via enzyme-assisted hydrolysis and subsequent homogenization. Field emission scanning electron microscopy (FE-SEM) confirmed the fiber morphology. The water retention value (WRV) was increased from 107% of original pulp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The dominant peaks of OH-stretching and CH-stretching at 3450 cm −1 and 2920 cm −1 were presented in the entire spectra [26]. The peaks at 896 cm −1 and 1061 cm −1 were associated with C-H deformation vibrations and C-O-C stretching vibrations, respectively, these data showed typical cellulose structural characteristics as reported in many previous studies [27,28]. The band at 1460 cm −1 , 1514 cm −1 and 1596 cm −1 were assign to C-H deformation vibration, aromatic skeletal vibration and C=C benzene ring vibration of lignin, respectively [29,30].…”
Section: Resultssupporting
confidence: 78%
“…The dominant peaks of OH-stretching and CH-stretching at 3450 cm −1 and 2920 cm −1 were presented in the entire spectra [26]. The peaks at 896 cm −1 and 1061 cm −1 were associated with C-H deformation vibrations and C-O-C stretching vibrations, respectively, these data showed typical cellulose structural characteristics as reported in many previous studies [27,28]. The band at 1460 cm −1 , 1514 cm −1 and 1596 cm −1 were assign to C-H deformation vibration, aromatic skeletal vibration and C=C benzene ring vibration of lignin, respectively [29,30].…”
Section: Resultssupporting
confidence: 78%
“…26 The peaks at 1429, 1110, and 896 cm À1 indicated the typical structure of cellulose found in all samples, which revealed that there were no signicant structural changes aer the cross-linking reaction. 27 As the PAE content increased, a peak was observed around 1633 cm À1 , corresponding to the amide group belonging to PAE. 19 Compared to the neat TOCN lm, a new band was observed around 1718 cm À1 , which was assigned to the C]O vibrations from the ester functions in the crosslinking network.…”
Section: Structure Of the Tocn/pae Hybrid Lmsmentioning
confidence: 98%
“…The bands at 1592 cm −1 and 1460 cm −1 can be associated with the C=C benzene ring vibration of lignin and C-H deformation vibration, respectively [67]. The last two peaks at 1233 cm −1 and 1027 cm −1 are representative of the C-O stretching and the typical C-O-C stretching vibrations of cellulose [68], respectively. The exposure to the UV-B radiation results in an increase in the intensity of the peak at 1729 cm −1 , which is accompanied by a reduction in the signal of the peak at 1233 cm −1 .…”
Section: Uv-b Exposurementioning
confidence: 98%